THE MUNICIPAL LEGAL AWARENESS: STRUCTURAL ANALYSIS - Denis O. Bobrovnyk (Alfred Nobel University Journal of Law)
The article is devoted to the study of the structure of municipal legal consciousness, which plays a special role (along with municipal psychology) in the processes of forming the globalist potential of the territorial community. This is the first time that this topic has been studied in domestic law. The author notes that the structure of municipal legal awareness, as well as the general phenomenology of legal awareness, consists of the following elements: legal (municipal-legal) psychology, legal (municipal-legal) ideology and legal (municipal-legal) behavior. The author asserts that, as a phenomenon, legal profile psychology a priori arises at the municipal-legal level, that is, at the local level of the existence of society, because it is the person, his groups and associations that exist and function precisely at the level of territorial communities. Legal (municipal-legal) ideology, as a structural element of municipal legal awareness, encompasses knowledge, ideas, concepts about the content of law, including municipal law normative regulations, which are formed as a result of legal education and legal scientific research. The author considers that, unlike municipal legal psychology, which is formed mainly spontaneously, depending on subjective events in municipal life and the experience of past generations, municipal legal ideology is formed in a systemic way as a result of: a) scientific (doctrinal), theoretical reflection of the municipal legal reality, b) based on the generalization and development of the most famous and significant municipal legal theories of the past and present; c) study of the main regularities of the formation, development and functioning of municipalism and its regulatory support and maintenance; d) study of the fundamental principles of municipalism, which are enshrined in international legal standards of local democracy; e) study of the basic principles of the state municipal policy. The author emphasizes that the municipal-legal ideology has a direct impact on the formation, modernization and modification of the bases of the municipal-legal psychology, making its instructions more applicable to the changes associated with the various manifestations of globalization. The third element of municipal legal consciousness is legal (municipal-legal) behavior, which involves its volitional side, which is the process of transforming the norms of municipal law into real municipal-legal behavior of a person within territorial communities. The author emphasizes that local self-government bodies, especially representative ones, can also act within the framework of using the principles of municipal-legal behavior, because they, actually speaking on behalf of the territorial community and in its interests, relay the relevant guidelines of municipal-legal psychology and municipal-legal ideologies possessed by the local human community. The article states that the daily municipal legal reality is carried by all residents of the respective territorial communities at the planetary level. In turn, the municipal legal reality acts as a catalyst for the formation and development of the globalization potential of the territorial community.